Designing model of performance measurement system of sugar industry cluster based on integrated performance measurement system approach - Partiwi, S G; Agusta, Y R (Institut Teknologi Sepuluh Nopember, 2018)
The Indonesian need for sugar is not balanced with domestic sugar production. This is reinforced by the fact that Indonesia is still a sugar importing country since the 1990s. Since 2010 - 2014, Indonesia's import value reaches 1.7 million US every year. This situation indicates mismatch with the roadmap of the sugar industry which is expected by 2015 to 2020. East Java as one of the largest contributor of Indonesian sugar with a contribution percentage of 52.31% of the overall national production has an important role in the development of the sugar industry. Therefore, a comprehensive sugar industry cluster development strategy is needed to be developed.Â The design of performance measurement system with Integrated Performance Measurement System (IPMS) approach was chosen by selecting PT 'X' as the core agent. The research stages are identification of sugar industry cluster system, stakeholder requirement and objective, Key Performance Indicator (KPI) formulation and model development. Development of performance measurement model by determining aspects and criteria of success of industrial cluster, weighting on each element using Analytical Hierarchy Process (AHP), and designing scoring board to facilitate implementation. There were 4 aspects in performance measurement, 9 criteria, 3 sub criteria and 45 KPIâ€™s.